2014
DOI: 10.1371/journal.pone.0111861
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cotton Leaf Curl Virus Resistance in BC1, BC2, and BC3 Progenies from an Interspecific Cross between Gossypium arboreum and Gossypium hirsutum

Abstract: Cotton leaf curl virus disease (CLCuD) is an important constraint to cotton production. The resistance of G. arboreum to this devastating disease is well documented. In the present investigation, we explored the possibility of transferring genes for resistance to CLCuD from G. arboreum (2n = 26) cv 15-Mollisoni into G. hirsutum (2n = 52) cv CRSM-38 through conventional breeding. We investigated the cytology of the BC1 to BC3 progenies of direct and reciprocal crosses of G. arboreum and G. hirsutum and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In BC 3 , substantial number of plants retained significant number of bolls because of the high frequency of chromosome pairings (bivalents). Thus, this study has shown successful introgression of resistant genes from G. arboreum to G. hirsutum ( Nazeer et al, 2014 ).…”
Section: Strategies For Controlling the Diseasementioning
confidence: 71%
“…In BC 3 , substantial number of plants retained significant number of bolls because of the high frequency of chromosome pairings (bivalents). Thus, this study has shown successful introgression of resistant genes from G. arboreum to G. hirsutum ( Nazeer et al, 2014 ).…”
Section: Strategies For Controlling the Diseasementioning
confidence: 71%
“…Cotton leaf curl disease (CLCuD) caused by CLCuV is a serious disease of cotton and several other malvaceous plant species transmitted by the whitefly Bemisia tabaci . No variety of Gossypium hirsutum has been reported as resistant against devastating virus whose carrier is whitefly [ 9 ]. This disease was reported in Pakistan and India but gradually it has spread to other cotton growing areas of the world, especially south China.…”
Section: Discussionmentioning
confidence: 99%
“…Epicuticular waxes in cotton are of different types and variation has been reported from species to species in terms of amount and composition [8]. Among these Asiatic cotton or Gossypium arboreum is well documented as resistant against CLCuD, not a single variety of Gossypium hirsutum has been reported as resistant against CLCuD [9]. Barozai and Husnain (2014) have reported a higher amount of wax in G. arboreum than G. hirsutum [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Its valuable traits include strengthened fiber, high seed index, and high oil content ( Mehetre et al, 2003 ). Additionally, resistances against biotic stresses viz; reniform nematode ( Erpelding and Stetina, 2013 ), tobacco budworm ( Hedin et al, 1992 ), Cotton leaf curl virus (CLCuV) ( Nazeer et al, 2014 ), and thrips ( Stanton et al, 1992 ) can possibly be introgressed to G . hirsutum .…”
Section: Introductionmentioning
confidence: 99%